1994
DOI: 10.4141/cjps94-005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immersing dry seeds in alkaline solutions on seed dormancy and water uptake in wild oat (Avena fatua)

Abstract: (Munay et al. 1980). Whether dormant wild oat seeds will respond to the alkaline solutions is unknown, to the best of our knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Combinations of afterripening period, ethephon (2-chloroethylphosphonic acid), and KNO 3 induced over 90% germination of seeds that were dormant at maturity (Saini et al 1985). A 5.3 N potassium hydroxide (KOH) solution for 10 min released dormancy in three A. fatua genotypes (Hou and Simpson 1994). Sodium hypochlorite (NaOCl) in combination with GA 3 solutions were effective in releasing dormancy in intact or dehulled A. fatua seeds Quick 1984, 1985).…”
Section: Reproductionmentioning
confidence: 99%
“…Combinations of afterripening period, ethephon (2-chloroethylphosphonic acid), and KNO 3 induced over 90% germination of seeds that were dormant at maturity (Saini et al 1985). A 5.3 N potassium hydroxide (KOH) solution for 10 min released dormancy in three A. fatua genotypes (Hou and Simpson 1994). Sodium hypochlorite (NaOCl) in combination with GA 3 solutions were effective in releasing dormancy in intact or dehulled A. fatua seeds Quick 1984, 1985).…”
Section: Reproductionmentioning
confidence: 99%
“…It is further suggested that these changes may atso increase the uptake of nitrate or other solutes that have been shown to stimulate germination. In support of this hypothesis, the apparent similarity and interaction between the effects of after-ripening and seed coat piercing on nitrate-induced germination could be attributed to their similar capacity to promote water and nitrate uptake by the embryo, ltijurious effects on the seed coat, and a consequent increase in water uptake by the embryo, might also account for the reported induction of germitiation in dormant seeds of A. fatua and other species by various toxic substances, e,g, cyatiides (Hendricks and Taylorson 1972), sodium azide (Fay and Gorecki 1978), sodium hypochlorite (Hsiao 1979) and ethanol (Adkins et al, 1984a), Hsiao (1979 suggested that a modification of the seed coat may have caused the induction of gemiination of dormant A. fatua caryopses by sodium hypochlorite, while a recent study by Hou and Simpson (1994) provided evidence tliat an increase in the hydraulic conductivity of the seed coat might be at least partly responsible for the breakitig of domiancy in several strains of A. fatua when the dry caryopses were treated with concentrated solutions of sodium hydroxide. Clearly, however, further investigation involving a wide range of species, and including the measurements of effects on the water Physiol,Plant,97,19% content of the embryo (Mclntyre and Hsiao 1985), would be required to assess the general validity of this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this approach was provided by previous evidence that, in this species, factors affecting water uptake by the embryo play a major role in determining the occurrence and degree of dormancy. In experiments with CS40', a genetic line of A. fatua with a relatively low degi'ee of dormancy (Naylor and Jana 1976), the rate of germination induced by piercing a hole in the upper (abaxial) surface of the imbibed caryopsis was inversely related to the distance of the hole from the embrj'O, and was increased by the application of water to the site of injury (Hsiao et al, 1983), Further investigations (Mclntyre and Hsiao 1985) showed that piercing the lower surface of the fully imbibed caryopsis raised the water content of the embryo to a higher plateau after 12 to 18 h. This initial response was followed, after a further 24 h, by a continuous increase in water uptake that was associated with root emergence, A similar pattern of response was induced by supplying water directly to embryos excised from imbibed caryopses. However, in contrast to the piercing response, the duration of the lag periods preceding the initial and subsequent increases in embryo water content were considerably reduced.…”
mentioning
confidence: 99%
“…are often manifested by the low and irregular germination, as observed in V. angustifolium, V. ashei, V. canadense, V. corymbosum, V. macrocarpon and V. oxycoccus [23]. In wild oat dormant seeds the use of KOH promoted significantly improvement on the germination [19]. Similarly seeds of Vaccinium angustifolium Ait.…”
Section: Resultsmentioning
confidence: 99%
“…The impermeability of the seed coat is a physical dormancy, which prevents the entry of water [16] and can be caused by the presence of substances such as suberin, lignin, cutin, tannins, pectins, as well as derivates of quinine [17]. Chemical studies indicate that the cuticle and pigment chains, present in the seed coat, are composed by insoluble polymeric materials, which can be depolymerized by alkaline hydrolysis [18] with KOH or NaOH [19].…”
Section: Introductionmentioning
confidence: 99%